Oxford case histories in anaesthesia - McCormack, Jon; Kelly, Keith (Anaesthetist) ([Oxford] : Oxford University Press, 2015)
Based around the core curriculum for specialist trainees in anaesthesia, this book contains over 60 clinical cases compiled by expert consultants. It covers all sub-specialties and many variations that occur in normal and abnormal physiology, pharmacology, and pathology and patient age.
Previously issued in print: 2014.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on August 15, 2016).
Keywords: Anesthesiology -- Case studies